2011
DOI: 10.1016/j.jval.2010.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of bivalirudin versus heparin plus glycoprotein IIb/IIIa inhibitor in the treatment of non–ST-segment elevation acute coronary syndromes

Abstract: Treating NSTE-ACS patients undergoing invasive management with bivalirudin is likely to represent a cost-effective option for the United Kingdom, when compared with the current practice of using heparin and a GPI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Guidance documents issued by NICE and by the Scottish Medicines Consortium were informed by the analysis presented here and by an earlier version reflecting the Scottish setting 12 37. A previous cost-effectiveness analysis for UK patients with NSTE-ACS used the same analytical framework but favoured bivalirudin less strongly than the present analysis 13. This result is consistent given smaller clinical effect sizes and longer anticoagulant and GPI administration times.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Guidance documents issued by NICE and by the Scottish Medicines Consortium were informed by the analysis presented here and by an earlier version reflecting the Scottish setting 12 37. A previous cost-effectiveness analysis for UK patients with NSTE-ACS used the same analytical framework but favoured bivalirudin less strongly than the present analysis 13. This result is consistent given smaller clinical effect sizes and longer anticoagulant and GPI administration times.…”
Section: Discussionsupporting
confidence: 86%
“…The long-term life expectancy of STEMI patients, utility values (ie, quality of life weights) and unit costs were drawn from UK sources. A similar approach was previously used in a cost-effectiveness analysis of bivalirudin in the treatment of non-ST-segment elevation acute coronary syndrome (NSTE-ACS) 13. Details on model assumptions and input parameters are provided below and in the online supplement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A cost-effective model from the UK perspective, that used data inputs from the ACUITY trial, also found bivalirudin to be cost effective (though not cost saving) 10. However, until the present study10a no economic evaluation of bivalirudin in patients with STEMI undergoing primary PCI has appeared in the literature.…”
mentioning
confidence: 67%
“…In this edition of Heart , Schwenkglenks et al 10a present a model-based cost-effectiveness analysis from the UK perspective of bivalirudin versus UFH + GPI for patients with STEMI, who were undergoing primary PCI, based on results from HORIZONS-AMI. Using a similar model structure as previously used in their ACUITY-based study,10 the authors report lower lifetime costs and increased quality-adjusted life expectancy with bivalirudin, with 95% of simulations rendering bivalirudin a dominant strategy. Although the results of these studies are not surprising, they do fill an important gap in the economic literature relating to bivalirudin, and were also instrumental in the recent approval of bivalirudin issued by the National Institute for Health and Clinical Excellence (NICE),11 for patients with STEMI, who were undergoing primary PCI, against the alternative of UFH + GPI.…”
mentioning
confidence: 98%